2016
DOI: 10.1002/cssc.201600702
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of pH Evolution of Electrolyte in the Reaction Mechanism for Rechargeable Zinc Batteries

Abstract: The reaction mechanism of α-MnO having 2×2 tunnel structure with zinc ions in a zinc rechargeable battery, employing an aqueous zinc sulfate electrolyte, was investigated by in situ monitoring structural changes and water chemistry alterations during the reaction. Contrary to the conventional belief that zinc ions intercalate into the tunnels of α-MnO , we reveal that they actually precipitate in the form of layered zinc hydroxide sulfate (Zn (OH) (SO )⋅5 H O) on the α-MnO surface. This precipitation occurs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
295
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(316 citation statements)
references
References 59 publications
(153 reference statements)
13
295
0
2
Order By: Relevance
“…[3a] However,t he mechanisms of aqueous ZIBs with ZnSO 4 electrolytes are still being debated, which are caused by the formation of Zn 4 (OH) 6 SO 4 ·n H 2 O(ZHS). [32] ZHS was generally regulated by the pH changes of the electrolytes during the discharge process,w hich could be formulized as [Eq. (8)]:…”
Section: Neutral or Mildly Acidic Electrolytesmentioning
confidence: 99%
“…[3a] However,t he mechanisms of aqueous ZIBs with ZnSO 4 electrolytes are still being debated, which are caused by the formation of Zn 4 (OH) 6 SO 4 ·n H 2 O(ZHS). [32] ZHS was generally regulated by the pH changes of the electrolytes during the discharge process,w hich could be formulized as [Eq. (8)]:…”
Section: Neutral or Mildly Acidic Electrolytesmentioning
confidence: 99%
“…where b is the Bruggeman coefficient, D i is the diffusion coefficient, z i is the charge number,a nd t i is the transference number of the solute. The convective flux of quasiparticle q is defined by Equation (18):…”
Section: Generic Formmentioning
confidence: 99%
“…Experimental studies show that zinc batteries based on these electrolytes can be reliably operated over hundreds or even thousands of cycles. [13,14,[16][17][18] However,t ok eep the pH value of the electrolyte in the near-neutral regime, ab uffer solution is required to counteract the effects of the oxygen-reductiona nd oxygen-evolution reactions. In the case of ZnCl 2 , this is accomplished by the addition of NH 4 Cl and NH 4 OH.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above reaction mechanisms mentioned, a chemical conversion reaction mechanism based on reversible precipitation/dissolution of Zn 4 (OH) 6 SO 4 · n H 2 O (ZHS) has also been proposed (Figure A) . For the first time, Oh et al found that the ZHS is obtained after fully discharging, and disappears after fully charging (Figure B).…”
Section: Manganese‐based Oxidesmentioning
confidence: 99%
“…Reproduced with permission from Ref. , Copyright 2016, Wiley‐VCH. C‐H, TEM/high resolution TEM images of MnO 2 electrodes during electrochemical process.…”
Section: Manganese‐based Oxidesmentioning
confidence: 99%